Corrosion Inhibition of 1,4-di (1-vinyl-3-methylimidazolium) Benzene Dibromide on Mild Steel in HCl Solution - Nahle,Ayssar (2016)
The inhibition and the effect of temperature and concentration of 1,4-di(1-vinyl-3methylimidazolium) benzene dibromide (VMIBB) on the corrosion of mild steel in 1.0 M HCl solution was investigated by electrochemical polarization and weight loss experiments at temperatures ranging from 303 to 343 K. The studied inhibitor concentrations ranged between 1.0×10-6 M and 1.0×10-2 M. The percentage inhibition increased with the increase of the inhibitor's concentration. The percentage inhibition has reached about 93 % at the concentration of 1×10-2 M and 303 K. On the other hand, the percentage inhibition decreased with the increase of temperature. Using the Langmuir adsorption isotherm, the thermodynamic parameters for the adsorption of this inhibitor on the metal surface were calculated. 1,4-di(1-vinyl-3-methylimidazolium) benzene dibromide was found to be a potential corrosion inhibitor, since it contained not only nitrogen, but also three aromatic systems, double bond, and it is a large molecule which has a big surface with high molar surface coverage.